IMPROVING READING COMPREHENSION OF THE TENTH GRADE STUDENTS AT SMA NEGERI 1 SOE THROUGH POSSE STRATEGY IN THE ACADEMIC YEAR OF 2021/2022 - Yabes Olbata; Marike Nelwan; Dessy Natty (Wiralodra English Journal, 2023)
The objective of this research is to improve reading comprehension of the tenth grade students at SMA Negeri 1 Soe through POSSE strategy. The type of the research was action research. The subjects of the research were 32 students of grade X Science 1 at SMA Negeri 1 Soe. There were two kinds of the data in this research were qualitative and quantitative. The qualitative data were obtained by doing observation, interviewing and field note. The quantitative data were obtained from the pre-test and post-test. They were presented in the form of scores and analyzed by using descriptive statistics in SPSS 17 program. The result showed that POSSE strategy allows students to have practices in predicting the text, organizing the prediction, searching the main idea, summarizing the text, and evaluating their understanding of the text. It also helped the students enrich their vocabulary by maximizing use of the predicting and the evaluating steps. Then, most students show their enthusiasm and active participation in the teaching and learning process of reading. Finally, there is an improvement on students’ reading comprehension. It could be concluded that POSSE strategy could improve students’ reading comprehension.